2016
DOI: 10.1128/jb.00529-16
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants for Antitoxin Identity and Insulation of Cross Talk between Homologous Toxin-Antitoxin Systems

Abstract: Toxin-antitoxin (TA) systems are ubiquitous in bacteria and archaea, where they play a pivotal role in the establishment and maintenance of dormancy. Under normal growth conditions, the antitoxin neutralizes the toxin. However, under conditions of stress, such as nutrient starvation or antibiotic treatment, cellular proteases degrade the antitoxin, and the toxin functions to arrest bacterial growth. We characterized the specificity determinants of the interactions between VapB antitoxins and VapC toxins from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…We expected each HipA toxin to be counteracted by binding to the HipB antitoxin encoded in its operon. Promiscuity between toxin and antitoxin partners is rare, even in bacteria harboring multiple paralogous toxins, but crosstalk in HipA-HipB interactions has never been investigated 36,37 . To determine the cognate HipB antitoxin(s) for each HipA toxin, we coexpressed all combinations of HipA and HipB in a ΔhipBA 1,2,3 background ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We expected each HipA toxin to be counteracted by binding to the HipB antitoxin encoded in its operon. Promiscuity between toxin and antitoxin partners is rare, even in bacteria harboring multiple paralogous toxins, but crosstalk in HipA-HipB interactions has never been investigated 36,37 . To determine the cognate HipB antitoxin(s) for each HipA toxin, we coexpressed all combinations of HipA and HipB in a ΔhipBA 1,2,3 background ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Type II TA systems, both toxin and antitoxin form a tight TA complex that binds to the operator region and results in auto-repression ( 17 ). The N-terminal domain of antitoxins possess DNA-binding properties, and the C-terminal domain neutralizes the toxin ( 18 , 19 ). Several DNA-binding motifs, such as ribbon-helix-helix (RHH), helix-turn-helix, AbrB and PhD/YefM, have been mapped to the N-terminal domain of antitoxins ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…6A). Accordingly, we changed the loop-closing G-C pair (31)(32)(33)(34)(35)(36)(37)(38)(39) in NTHi tRNA fMet-14 to A-U and measured the extent of its cleavage by VapC1 NTHi and VapC2 NTHi in vivo. The result revealed that the G-C-to-A-U mutation decreased cleavage of NTHi tRNA fMet-14 by 30 to 40%, suggesting that this G-C pair plays a key role in recognition of the substrate by VapCs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenic organism nontypeable Haemophilus influenzae (NTHi) contains two vapBC systems: vapB1C1 and vapB2C2. These two systems are homologous; however, there is no cross talk between them, as the antitoxins are highly specific for their cognate toxins (32). Studies have shown that these systems are upregulated during NTHi infection and facilitate enhanced survival and growth regulation (33,34).…”
mentioning
confidence: 99%